2022
DOI: 10.1063/5.0086303
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating acoustic Doppler velocimetry pulse-pair spacing/velocity range setting for turbulent flow measurements

Abstract: The velocity range, which is inversely proportional to acoustic pulse-pair spacing, is one of the most important user-set parameters of acoustic Doppler velocimeters (ADVs) and is expected to influence their flow measurements. An experimental study of the effect of the ADV velocity range on the mean and turbulence statistics measured in stagnant water, a turbulent channel flow, and a turbulent jet was undertaken. The results show that as long as the instantaneous velocities are within the user-set velocity ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…ADVs measure the three-dimensional velocities in the crossbeam and beamwise directions. It has been shown that the RMS velocities measured in the beamwise direction are accurate, while those measured in the crossbeam directions are overestimated because of Doppler noise (Khorsandi et al, 2012;Moeini et al, 2020;Nejatipour and Khorsandi 2021;Homayounfar and Khorsandi, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…ADVs measure the three-dimensional velocities in the crossbeam and beamwise directions. It has been shown that the RMS velocities measured in the beamwise direction are accurate, while those measured in the crossbeam directions are overestimated because of Doppler noise (Khorsandi et al, 2012;Moeini et al, 2020;Nejatipour and Khorsandi 2021;Homayounfar and Khorsandi, 2022).…”
Section: Methodsmentioning
confidence: 99%